Os gêneros textuais e sua contribuição para o processo de alfabetização nos anos iniciais do ensino fundamental - Silva, Paola Gualberto da (Brasil, 2024)
The present work deals with a bibliographic study with the objective of investigating in literature the contributions of textual genres to the development of reading and writing in initial literacy, as well as the analysis of six Portuguese language textbooks for literacy in the initial years of education. fundamental. It is known that contact with textual genres is fundamentally important for the development of reading and writing from early childhood education, extending to initial literacy and subsequent grades. For this to occur, it is up to the teacher to carry out an intentional pedagogical practice planned so that literacy students take ownership of the alphabetic writing system and its properties and, through textual genres, understand the everyday social functions of reading and writing in their community and society. The main authors with whom we discussed were: Emília Ferreiro and Teberosky (1999), Schneuwly and Dolz (2004), Soares (2003) and Zabala (1998). In the analysis and discussion of the results in the light of the authors, it was found that textual genres are the starting point of the literacy process, being a communicational linguistic resource that mediates and enriches the process of developing skills and competencies in reading and in the writing. When working with textual genres in the classroom, it is important to value the prior knowledge of literacy students, stimulating their interest in reading and writing so that they understand the message and content of the text, giving access to different cultures and realities through a virtual trip and imaginary. The work is structured into two chapters, the first “Alphabetizing literacy: the search for meaning in teaching and learning reading and writing in literacy”. In the second chapter we discuss textual typologies and textual genres: linguistic concepts and characteristics and the most recommended textual genres in Portuguese language textbooks for the literacy cycle.